Does free hospitalization insurance change health care consumption of the poor? Short-term evidence from Pakistan - Simona Helmsmüller; Andreas Landmann (The Geneva Risk and Insurance Review, 2021)
We analyze short-term effects of free hospitalization insurance for the poorest quintile of the population in the province of Khyber Pakhtunkhwa, Pakistan. First, we exploit that eligibility is based on an exogenous poverty score threshold and apply a regression discontinuity design. Second, we exploit imperfect rollout and compare insured and uninsured households using propensity score matching. With both methods we fail to detect significant effects on the incidence of hospitalization. Whereas the program did not meaningfully increase the quantity of health care consumed, insured households more often choose private hospitals, indicating a shift towards higher perceived quality of care.
Keywords: O12; I13; I15; O22; 330; Health insurance; Universal health care; Program evaluation; Health care consumption; Pakistan